Challenges for Micro, Small, And Medium Enterprises Facing Digitalization in Accounting - Setiawan, David Firna; Indriasari, Ika; Darmaputra, Mochamad Fadjar; Lestari, Utami Puji (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2024)
The labor market is not always able to meet the demand for workers who have competence in accounting. One of the sectors experiencing this condition is the owner of Desa tea shop in Semarang city. It certainly has an impact on the training and mentoring conducted by business owners to improve the competence of their employees. This study aims to look at the training and mentoring process carried out by the owner of the village tea shop employees in Semarang City. The research was conducted by surveying micro, small and medium enterprises (UMKM) or owners of Village Tea Shops. The results showed that the average time needed to train employees to perform work related to product presentation and transaction data input in the group of employees with low accounting competence (group 2) was longer than that of employees with medium and high accounting competence. In addition, the average time needed to assist employees to perform work related to product presentation and data input in the group of employees with low accounting competence is longer than that of employees with medium and high accounting competence. The results indicate that the lack of accounting competence of village tea shop employees has an impact on the owner's efforts to make employees have better work readiness. Further research can expand the population and research area so that the research results can be better generalized to provide an overview of the challenges of accounting digitalization in UMKM.